2018
DOI: 10.15244/pjoes/82900
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Land-Use and Vegetation Change Using NDVI and Transfer Matrix: A Case Study of the Huaihe River Basin

Abstract: The Huaihe River Basin is located in-between the north-south climate transitional zone in China and is China's important congested area and production base. The land-use of the environment was occupied by the land-use for social and economics. This paper aims to have a comprehensive understanding about land-use and vegetation evolution of the basin over the past 30 years. In view of 5 years (1985, 1990, 2000, 2005, and 2014) land-use data and remote sensing data about NDVI, land-use dynamic degree, and land-us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…It can be observed in this study that the spatial distribution of cultivated land resources in the Huaihe River Basin was relatively uniform, the Gini coefficient of cultivated land increased year by year, and the degree of cultivated land specialization was high, which is similar to the results obtained by Liu et al based on NDVI and the transfer matrix method [ 49 ]. Previous studies have shown that cultivated land in mountainous and hilly areas was more inclined to show the spatial separation characteristics of land structure than that in plain areas [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…It can be observed in this study that the spatial distribution of cultivated land resources in the Huaihe River Basin was relatively uniform, the Gini coefficient of cultivated land increased year by year, and the degree of cultivated land specialization was high, which is similar to the results obtained by Liu et al based on NDVI and the transfer matrix method [ 49 ]. Previous studies have shown that cultivated land in mountainous and hilly areas was more inclined to show the spatial separation characteristics of land structure than that in plain areas [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…We used three methods to analyze the temporal and spatial characteristics of LUCC in Laos, which are a land use transfer matrix [49], a landscape pattern index, and a topographic overlap analysis. The land use transfer matrix identified the intensity and direction of the conversion between various land uses, so that the quantity and structural characteristics of the LUCC during the study period could be analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…e statistical Kappa coe cient classication accuracy recommended value ranges from 0.18 to 0.99. us, the result in this study is considered almost in perfect agreement based on the Kappa Statistics. is implies that the change detection results could be used for further analysis as land cover transformation matrix and ArcGIS 10.4 were employed to analyze a comprehensive land use dynamics degree [40].…”
Section: Classification Of Land Cover Type and Change Detectionmentioning
confidence: 99%
“…A vegetation cover is an important factor that could change the ecosystem and the hydrology pattern in the basin, thereby causing climate variability. Vegetation dynamics could change the global carbon and hydrology cycle as well as climate change [40]. e overlaps of the NDVI, EVI maps of 2001 and 2013, and climatic variations of the current weather show a high degree of climate change occurring across the basin.…”
Section: Measuring Vegetation (Ndvi and Evi)mentioning
confidence: 99%